HUBUNGAN ANTARA EFIKASI DIRI DAN DUKUNGAN SOSIAL GURU DENGAN PENGAMBILAN KEPUTUSAN KARIR STUDI LANJUT KE PERGURUAN TINGGI PADA SISWA SMA DI KABUPATEN KUDUS - Ayu Wulandari, Sekar; Hervi Mahardayani, Iranita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine the relationship between self-efficacy and teacher social support with career decision-making for continuing studies to higher education among senior high school students in Kudus Regency. This research used a quantitative correlational approach with 34 twelfth-grade students who were in the stage of deciding to continue their studies to higher education. The sampling technique used quota sampling. Data were collected using career decision-making, self-efficacy, and teacher social support scales based on relevant theoretical aspects. Data were analyzed using correlation and multiple linear regression with SPSS 27.0 for Windows. The results showed a very significant relationship between self-efficacy and teacher social support with career decision-making (r = 0.570; p < 0.01). In addition, self-efficacy and teacher social support were positively related to career decision-making. These findings indicate that higher self-efficacy and teacher social support are associated with better career decision-making among students.